A familial analysis of two brothers with azoospermia caused by maternal 46, Y, t(X; 1) (q28; q21) chromosomal abnormality. (3rd November 2020) - Li, Youzhu; Sha, Yanwei; Wei, Zijie; Liu, Wensheng; Mei, Libin; hong, Yun; Jiang, Lizhi; Ge, Yunsheng; Xie, Yuanzhi
Abstract: Chromosomal abnormality is a primary genetic factor that lead to azoospermia and male infertility. Here, we report the cases of two brothers with primary infertility, whose chromosomes displayed a balanced translocation, and their karyotypes were 46, Y, t(X; 1) (q28; q21). Both presented an azoospermia phenotype without abnormal clinical symptoms. Their mother's karyotype was 46, X, t(X; 1) (q28; q21), and their father's chromosome karyotype was 46, XY. No abnormal changes were noted in the copy number of chromosome fragments in the whole genome. This study is the first to report showing that 46, Y, t(X; 1) (q28; q21) chromosomal abnormalities are associated with azoospermia.